2012
DOI: 10.1007/s11606-012-2161-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving Test Result Follow-up through Electronic Health Records Requires More than Just an Alert

Abstract: A recent American Medical Association report highlighted failures in communication of abnormal test results as an important but understudied facet of improving safety in ambulatory care. 1 Because many outpatient test results are not life-threatening and don't require verbal communication, health information technology (IT) has potential to reliably transmit result information in the fragmented outpatient setting. Thus, few will disagree that communication of abnormal test results is an obvious context where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Although the result is entered into the patient’s electronic record, the ordering physician is not alerted and does not view the result until the patient’s follow up visit several weeks later. In this instance, the lack of a direct computerized provider order entry (COPE) system created the opportunity for transcription errors, and the absence of a two-way system-to-system interface for ordering tests prevented the results from being routed to the ordering provider once it became available [35]. …”
Section: Complexities Around Communication Of Test Resultsmentioning
confidence: 99%
“…Although the result is entered into the patient’s electronic record, the ordering physician is not alerted and does not view the result until the patient’s follow up visit several weeks later. In this instance, the lack of a direct computerized provider order entry (COPE) system created the opportunity for transcription errors, and the absence of a two-way system-to-system interface for ordering tests prevented the results from being routed to the ordering provider once it became available [35]. …”
Section: Complexities Around Communication Of Test Resultsmentioning
confidence: 99%
“…Evaluation dimensions can often be anticipated by addressing the eight dimensions of the model. 33,34 Experience with several studies 31,[35][36][37] has revealed that consideration of all eight dimensions of the sociotechnical model is essential to an understanding of successful implementation, use and evaluation of health IT-related interventions. Many of these dimensions were addressed in the case study, as detailed below.…”
Section: Teaching Point 1: An Evaluation Framework For Health It Mustmentioning
confidence: 99%
“…Similarly, external factors such as reimbursement systems, legal considerations, national quality measurement initiatives, accreditation and other policy and regulatory requirements all have influence on the success of health IT-based communication interventions. 33 The case study recognized these external rules and regulations by considering referral rates and their possible impact on health systems participating in global payment or shared savings contracts.…”
Section: Teaching Point 3: Always Consider the Impact Of Internal Or mentioning
confidence: 99%
“…In continuation of this finding, systems that rely on clinicians to "pull" information from the system are not sufficient [11], partly because critical results are overlooked and partly because clinicians waste time accessing the system in vain before the results are available. The alternative approach of "pushing" information to physicians by means of alerts does, however, not ensure consistent follow-up on test results [25]. Physicians who receive a large number of alerts may, for example, experience alert fatigue and stop reacting promptly to alerts [24].…”
Section: Working With Blood Testsmentioning
confidence: 99%